(untitled) (Global Journal of Human-Social Science, 2014)
Language verbal or non-verbal is central to the survival of mankind because it is an important tool for communication negotiation and the transfer or preservation of the literary as well as cultural heritage of a people from one generation to the other The relationship between language literature and culture is so strong to the extent that a change in one ultimately affects the other two Every language is a directly mirrors the culture it serves - a language either enriches or impoverishes the culture it serves Therefore the influence of language on the culture and literature of a people has dire consequences for the sustenance or development of their indigenous education Nigeria like the rest of the world has joined the terrace of globalization which has led to the import of foreign language s literatures and cultures into the indigenous way of life and system of education Currently increasing quest for the language literature and culture of the developed countries of the world which are projected by globalization has denied the Nigerian child access to his her indigenous system of education A system of education which is rich in fables taboos folklores and cultural rites rituals is gradually being crushed under the weight and demand of globalization This trend is common in Africa and it portends danger for the continued survival of the continent s indigenous language literature and culture This paper therefore posits that there is a need for Africans Nigerians to preserve and promote what is left of their indigenous language literature and culture through the use of an indigenous system of education The paper concludes by recommending practical ways of making use of the indigenous system of education within formal school system This is the only way that the people s indigenous way of life will survive the onslaught of globalization beyond the 21st century